A 21-year retrospective outcome study of New South Wales forensic patients granted conditional and unconditional release. (March 2014) - Hayes, Heather; Kemp, Richard I; Large, Matthew M; Nielssen, Olav B
Aim: To retrospectively examine the outcomes of forensic patients found not guilty by reason of mental illness (NGMI) in New South Wales (NSW) and subsequently released into the community, as measured by reoffending, conditional release revocation and psychiatric hospital readmission. Method: Data were collected from the NSW Mental Health Review Tribunal (MHRT) files for all patients who received an NGMI verdict between January 1990 and December 2010, and who were released into the community during this period. The outcome measures of conditional release revocation and psychiatric hospital readmission were extracted from these files. Information about subsequent criminal charges, convictions and penalties were obtained from the Bureau of Crime Statistics and Research's reoffending database. Results: During the 21-year period studied, 364 offenders received an NGMI verdict and were placed under the supervision of the MHRT. Of these, 197 were released into the community, including 85 who were granted unconditional release. Over a follow-up period averaging 8.4 years, 18% of conditionally released patients reoffended, 11.8% were convicted of a further offence, 8.7% were charged with a violent offence, 3.1% were convicted of a violent offence and 3.7% were sentenced to a term of imprisonment. Five (3.1%) conditionally released forensic patients received a further NGMI verdict. One-quarter of the conditionally released patients had their conditional release revoked and half were readmitted to hospital. Of the forensic patients granted unconditional release, 12.5% were charged with an offence, 9.4% received convictions for an offence, 6.3% were charged with a violent offence and 4.7% were convicted of a violent offence, in a mean follow-up period of 7.6 years. None committed a further serious offence resulting in a term of imprisonment, nor a second NGMI verdict. Conclusions: The results of this study suggest that the treatment and rehabilitation of forensic patients in NSW, together with the decision-making procedures of the MHRT, is effective in protecting the community from further offending by forensic patients.